RB distribuidora: sua história e o processo de formulação e implementação de estratégia - Carvalho, Hélvio Benedito Dias de (2004)
This dissertation analyzes the process of creating and improving strategies, in particular, the strategy formulation and implementation by RB Distributor. This company is a wholesale distributor of groceries and health care products in the state of Ceará. The study shows that a formal and structured process of strategic planning can add value to the strategic management of any company. This process gives direction to the formulation of strategies and goals which may increase their capacity to face the competitive forces in the market place. As such, RB Distributor has formulated its plan, its strategies and goals with a look into the future and its competitors. However, barriers and market changes influence the process of implementation of strategies and the attainment of its goals. In fact, RB Distributor faced those problems and this influenced adversely its results. A systematic feedback system of information and monitoring is recommended as a tool to reduce the negative impact those variables could have on the desired results.